Komparasi Usahatani Cabai Lahan Sawah Lereng Gunung Merapi dengan Lahan Pasir Pantai - Nugroho, Agus Dwi; Prasada, I Made Yoga; Putri, Saraswati Kirana; Anggrasari, Herdiana; Sari, Pinjung Nawang (AGRARIS: Journal of Agribusiness and Rural Development Research, 2018)
The main production areas of chilli inÂ Yogyakarta Province are in the wetland onthe slopes of Mount Merapi and in theÂ sandy coastal area. This research was intended to compare the use of productionÂ inputs, technical efficiency and performanceÂ of chilli farming in both areas. The researchÂ was conducted in Pakem sub-district andÂ Panjatan sub-district. The number of respondents in this research were 30 farmersÂ in every sub-district. Descriptive analysis,Â frontier analysis and revenue-cost ratio wereÂ used in this research. The results indicatedÂ that the use of production inputs, production, technical efficiency, and performanceÂ of chilli farming in the sandy coastal areaÂ was higher than that in the wetland. TheÂ technical efficiency in the wetland on theÂ slopes of Mount Merapi was determinedÂ by the quantity of counselling while in the sandy coastal area was determined byÂ the quantity of counselling and farmersâ experience. The auction market in bothÂ areas proved able to increase the price of chilli. It is highly recommended thatÂ the extension officers need to be active in assisting farmers in both areas, especially related with chilli cultivation and processing technology.